THE INFLUENCE OF END-STAGE LIVER DISEASE AND LIVER TRANSPLANTATION ON THYROID HORMONES - PENTEADO,Karla Rocha (2015)
Background Thyroid dysfunction has been reported in most chronic illnesses including severe liver disease. These defects in thyroid hormone metabolism result in the sick euthyroid syndrome, also known as low T3 syndrome. Objectives Our objective was to evaluate the thyroid function in patients with end stage liver disease prior and after deceased donor liver transplantation and to correlate thyroid hormonal changes with the MELD score (Model for End stage Liver Disease). Methods In a prospective study, serum levels of thyrotropin (thyroid stimulating hormone TSH), total thyroxine (tT4), free thyroxine (fT4) and triiodothyronine (T3) from 30 male adult patients with end stage liver disease were measured two to four hours before and 6 months after liver transplantation (LT). MELD was determined on the day of transplant. For this analysis, extra points were not added for patients with hepatocellular carcinoma. Results The patients had normal TSH and fT4 levels before LT and there was no change after the procedure. Total thyroxine and triiodothyronine were within the normal range before LT, except for four patients (13.3%) whose values were lower. Both hormones increased to normal values in all four patients after LT (P=0.02 and P<0.001, respectively). When the patients were divided into two groups (MELD <18 and MELD >18), it was observed that there was no change in the TSH, freeT4, and total T4 levels in both groups after LT. Although there was no significant variation in the level of T3 in MELD <18 group (P=0.055), there was an increase in the MELD >18 group after LT (P=0.003). Conclusion Patients with end stage liver disease subjected to liver transplantation had normal TSH and fT4 levels before and after LT. In a few patients with lower tT4 and T3 levels before LT, the level of these hormones increased to normal after LT.